CHARACTERIZATION OF THE LOAD‐SLIP BEHAVIOUR OF HEADED STUD SHEAR CONNECTIONS IN NARROW PROFILED SHEETING. Issue 1 (26th April 2023) - Vigneri, V.; Odenbreit, C.; Schäfer, M.; Hicks, S.; Lam, D.; Hanus, F.
Abstract: Although headed stud shear connections in profiled sheeting represent an efficient solution to transfer the longitudinal shear along composite beams, current EN 1994‐1‐1 may overestimate their design resistance in case of open trough profile steel sheeting with narrow ribs. Project team CEN/TC250/SC4.T3 proposed new equations based on a "cantilever" model which depends on the concrete tensile strength and the bending resistance of the connector. However, by increasing the slips, the internal forces redistribute, and the system can be represented by a "modified strut and tie" model. At large displacements, a "strut and tie" model was also developed accounting for the influence of the tensile forces in the connector. The respective analytical equations for predicting the load per stud were finally derived and compared with experimental load‐slip curves. It was found that the analytical models proposed lead to satisfactory predictions of the load‐slip behaviour of the shear connection.